Imperfect Tagging Revisited - Eric Rehn (Lund University, School of Economics and Management, Department of Economics, 2007)
Revisiting Parsons' 1996 article about disability insurance with imperfect tagging in a two type-economy – individuals are either able or disabled. Here Parsons' analysis is extended in several directions. The model is generalized to allow for different utility functions over work status. The analysis extends to three different cases of a two-type economy. Finally Parsons' model is extended to three types: able, partially disabled and disabled - adapting the model to disability insurances allowing for more than two degrees of disability. The results are consistent with Parsons', but a complete ranking of the consumption allocations cannot be achieved in the general case.
Keywords: H21; H53; 330; social insurance; imperfect tagging; partial disability